(untitled) (REVISTA NERA, 2023)
Understanding the reality of Socio-Territorial Movements and the process of struggle for land in the Amazon involves a deeper analysis of the cruelty and specialized extermination of certain stakeholders and organizations that lead the struggle and resistance. Our objective in this work is to discuss the total lack of interest and the necropolitics created on different profiles (peasants, leaders, unionists, landless, squatters, settlers, and other stakeholders), in addition to the way in which the extermination process manifests itself as part of the reality of the agricultural frontier in the Amazon. After an extensive and dedicated analysis of data by the Pastoral Land Commission (CPT), including interviews, mapping and analysis of journalistic material, we were able to conclude that the main way to promote the real preservation of the Amazon and its territories is through policies that care for the safety of living people. After all, the scenario presented in recent decades is that there is a permanent and systematic process that points to the specialization of murders of less favoured class leaders as a way of investing in obtaining land and illegal property in the Amazonian region of the state of Pará.